2010
DOI: 10.1111/j.1574-6968.2009.01887.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual and co-operative roles of lactic acid and hydrogen peroxide in the killing activity of enteric strain Lactobacillus johnsonii NCC933 and vaginal strain Lactobacillus gasseri KS120.1 against enteric, uropathogenic and vaginosis-associated pathog

Abstract: The mechanism underlying the killing activity of Lactobacillus strains against bacterial pathogens appears to be multifactorial. Here, we investigate the respective contributions of hydrogen peroxide and lactic acid in killing bacterial pathogens associated with the human vagina, urinary tract or intestine by two hydrogen peroxide-producing strains. In co-culture, the human intestinal strain Lactobacillus johnsonii NCC933 and human vaginal strain Lactobacillus gasseri KS120.1 strains killed enteric Salmonella … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(71 citation statements)
references
References 66 publications
(107 reference statements)
2
68
1
Order By: Relevance
“…Coaggregation of bacteria with harmful microorganisms has been considered as a protective mechanism against infection (Collado et al, 2008), and has been described in Lactobacillus (Pascual et al, 2008) and in Bifidobacterium (Del Re et al, 2000;Vlková , Rada, Smehilová , & Killer, 2008) from human origin. The mechanism underlying the protective activity of certain beneficial strains against bacterial pathogens appears to be multifactorial, where a co-operative antimicrobial effect might be considered (Atassi & Servin, 2010).…”
Section: Antimicrobial Activity and Identification Of Strainsmentioning
confidence: 99%
“…Coaggregation of bacteria with harmful microorganisms has been considered as a protective mechanism against infection (Collado et al, 2008), and has been described in Lactobacillus (Pascual et al, 2008) and in Bifidobacterium (Del Re et al, 2000;Vlková , Rada, Smehilová , & Killer, 2008) from human origin. The mechanism underlying the protective activity of certain beneficial strains against bacterial pathogens appears to be multifactorial, where a co-operative antimicrobial effect might be considered (Atassi & Servin, 2010).…”
Section: Antimicrobial Activity and Identification Of Strainsmentioning
confidence: 99%
“…The antimicrobial effect of lactic acid is not just due to the lowering of the intracellular pH. Indeed, hydrogen peroxide produced by L. johnsonii NCC 533 and other L. johnsonii strains in vitro kills S. Typhimurium (133), an effect enhanced in the presence of the membrane permeabilizer lactic acid (132). As deduced from in vitro experiments that have tested the sensitivities of secreted compounds present in L. rhamnosus GG, L. johnsonii NCC 533, and L. acidophilus LB CFCSs to a set of physical and chemical treatments and from partial isolation experiments, bactericidal activity against S. Typhimurium results from small (dialysis cutoff, 1,000 Da), nonproteinaceous compounds (120,122,123).…”
Section: Direct Activities Against Enterovirulent Bacteriamentioning
confidence: 99%
“…Indeed, the production of antimicrobials is often regarded a priori as an important trait in the context of bacterial fitness but also in terms of probiotic efficacy. Several probiotic bacteria produce a variety of antimicrobial compounds (e.g., short-chain fatty acids, hydrogen peroxide, nitric oxide, bacteriocins) that may enhance their ability to compete against other GI microbes and which could potentially inhibit pathogenic (disease-causing) bacteria (1,6). Traditionally, bacteriocin production has been an important criterion in the selection of a probiotic strain, albeit that few studies have definitively demonstrated the impact of bacteriocin production on the ability of a strain to compete within the GI tract and/or positively influence the health of the host (9).…”
mentioning
confidence: 99%